Challenging granulomatous differential diagnosis of CNS lesions in a 75-year-old patient with indolent lymphoma - Thurner, Lorenz; Melivadze, Ketevani; Matschke, Jakob; Topalidis, Theodoros; Bachhuber, Armin; Speicher, Tilman; Rosar, Florian; Reischl, Udo; Tränkenschuh, Wolfgang; Friesenhahn-Ochs, Bettina; Fries, Peter; Becker, Sören L.; et al. (Frontiers in Immunology, 2024)
We report here on a patient with concomitant indolent lymphoma who showed a rapid progressive deterioration of his general condition and emerging neurological symptoms. The combination of severe B symptoms with hypermetabolic involvement of the adrenal glands and multiple central nervous system (CNS) lesions initially suggested a malignant disease. However, when the patient presented to us with biopsy results from one of the CNS lesions, the biopsy revealed granulomatous inflammation but no evidence of malignancy. This case illustrates the difficulties and challenges of diagnosing in a timely manner Histoplasma capsulatum, an ultra rare infectious disease in Europe.